"It Was the Worst of Times, It Was the Worst of Times": Brexit and Literary Mood in Ali Smith's Autumn. (2nd June 2022) - Adam, Sibyl
Abstract: Ali Smith's Autumn is widely regarded as one of the most significant Brexlit novels to be published since the UK voted to leave the European Union in a referendum on 23 June 2016. This article analyzes the novel's use of mood, which is generated simultaneously through representations of collective emotional reactions, an innovative temporal structure, and through a reworking of the state-of-the-nation novel tradition. The relationship between the nation and the novel is developed through temporality, where historical and contemporary collective feelings of crisis unify the nonchronological narrative sequence. This article makes an intervention into discussions of Brexlit by foregrounding the use of mood as a regulator of multiple temporalities and nonchronological structural engagements with time as more useful than conventional realism in conveying the national impact of Brexit.